Blindness and children : an individual differences approach - Warren, David H. (Cambridge University Press, 1994)
"A summary and interpretation of the research literature on infants and children with visual impairments. It concludes that many aspects of delayed development are the result not of visual impairment itself, but of an environmental variables that tend to accompany visual impairment."